The selection of learning materials from Youtube resources for a Maritime English Course - Simbolon, Nurmala Elmin; Febrianti, Yusnita (Indonesian Journal of Applied Linguistics, 2020)
The use of YouTube resources as learning materials becomes increased in English language teaching (ELT), especially when implementing the content-based instruction (CBI) approach. In addition to its importance during the recent global restriction caused by the Corona Virus Disease (COVID-19), one of the benefits of using YouTube is perceived to provide authentic learning, which can improve the student learning experience, hence prepare graduates in the future career. While several studies have shown the benefits of using videos in ELT classrooms, this study argues that consideration for suitability and relevance of the visual materials should include the contained meaning potentials; experiential, interpersonal, and textual aspects. The study analyzed three videos used as teaching and learning materials in a Maritime English course at a vocational university where the research was conducted. Foregrounded by SFL theories, the analysis of the videos utilized Multimodal Video Analysis (MMA) Software to present a selection process of teaching and learning materials in the form of YouTube videos. Findings show the specifics of the meaning potentials in the videos used for the teaching and learning materials of the Maritime English course. The results also highlight the positive qualities and drawbacks identified in the videos. Additionally, the findings of the study provide guidelines for selecting video materials suitable and relevant to the Maritime English course in vocational higher education in Indonesia.